VENEREOLOGY IN INDIA - Thappa, Devinder Mohan (Medknow Publications, 2011)
Venereology-the study of venereal diseases or more recently, the sexually transmitted infections (STI) includes a variety of pathogens namely viruses, bacteria, fungi and protozoa for which the common factor is the mode of transmission and acquisition: Sexual relations between human beings. Medical and other historians have often suggested that well-known diseases such as syphilis, gonorrhea, chancroid and lymphogranuloma venereum have existed since earliest times. However, it is difficult to identify modern disease entities based on written historical record. Studying the origin of STIs helps us to learn the political, economic and moral conditions that led to the disease. Effective management of STI rests on three pillars of diagnosis, prevention and treatment. For most of past 50 years in India, the diagnostic pillar has been the least well-supported. Until well into present century, diagnosis of STI in India was clinical. Treatment of STIs in India followed the methods used in England. Of course in the 19(th) century, in many parts of the world, only a few had access to modern methods of treatment; in India, there was extensive use of Ayurvedic treatment with traditional medicines. This article thus gives just an overview and evolution of venereology in India with regard to venereal diseases (now more often known as STIs/disease), control measures, academic, association and journal development and finally future perspective.